Absorbable Artificial Dura Versus Nonabsorbable Artificial Dura in Decompressive Craniectomy for Severe Traumatic Brain Injury: A Retrospective Cohort Study in Two Centers - Zhang, Zhong-Ding; Zhao, Li-Yan; Liu, Yi-Ru; Zhang, Jing-Yu; Xie, Shang-Hui; Lin, Yan-Qi; Tang, Zhuo-Ning; Fang, Huang-Yi; Yang, Yue; Li, Shi-Ze; Liu, Jian-Xi; Sheng, Han-Song (Frontiers in Surgery, 2022)
Background: Severe traumatic brain injury (TBI) patients usually need decompressive craniectomy (DC) to decrease intracranial pressure. Duraplasty is an important step in DC with various dura substitute choices. This study aims to compare absorbable dura with nonabsorbable dura in duraplasty for severe TBI patients. Methods: One hundred and three severe TBI patients who underwent DC and dura repair were included in this study. Thirty-nine cases used absorbable artificial dura (DuraMax) and 64 cases used nonabsorbable artificial dura (NormalGEN). Postoperative complications, mortality and Karnofsky Performance Scale (KPS) score in one year were compared in both groups. Results: Absorbable dura group had higher complication rates in transcalvarial cerebral herniation (TCH) (43.59% in absorbable dura group vs. 17.19% in nonabsorbable dura group, P=0.003) and CSF leakage (15.38% in absorbable dura group vs. 1.56% in nonabsorbable dura group, P=0.021). But severity of TCH described with hernial distance and herniation volume demonstrated no difference in both groups. There was no statistically significant difference in rates of postoperative intracranial infection, hematoma progression, secondary operation, hydrocephalus, subdural hygroma and seizure in both groups. KPS score in absorbable dura group (37.95±28.58) was statistically higher than nonabsorbable dura group (49.05±24.85) in one year after operation (P=0.040), while no difference was found in the rate of functional independence (KPS≥70). Besides, among all patients in this study, TCH patients had a higher mortality rate (P=0.008), lower KPS scores (P<0.001) and lower functionally independent rate (P=0.049) in one year after surgery than patients without TCH. Conclusions: In terms of artificial biological dura, nonabsorbable dura is superior to absorbable dura in treatment of severe TBI patients with DC. Suturable nonabsorbable dura has fewer complications of TCH and CFS leakage, and manifest lower mortality and better prognosis. Postoperative TCH is an important complication in severe TBI which usually leads to a poor prognosis.